Rancang Bangun Aplikasi Manajemen Penjualan Konsyinasi Pada Perusahaan Dagang - Suwandi Suwandi; Aldo Hermaya Aditiya Nur Karsa; Marsani Asfi (Syntax Corporation Indonesia, 2024)
Habib Mart Cirebon is a trading company that distributes various Hajj souvenirs such as dates, koko clothes, prayer mats, zam-zam water, and others. Consignment sales management is becoming a key element in the trading industry, ensuring product availability, stock monitoring and accurate sales reporting. This research aims to design and develop a consignment sales management application to improve the operational efficiency of the Habib Mart Trading Company in Cirebon. The Waterfall software development method was chosen to ensure structured and planned development stages. It is hoped that the results of this research can contribute to improving operational efficiency and more timely managerial decisions at the Habib Mart Trading Company. In addition, the designed application can also be adapted by other trading companies to improve their consignment sales management..